The Emigration of the Algerian Elite to Tunisia in the Nineteenth Century: the Reasons & the Challenges - rouabhi, Ayachi (The Algerian Historical Journal, 2026)
During the 19th c, the Algerian Elite emigrated to Tunisia in order to escape from French abuses when they felt oppressed by the unfair occupier. Another push-factor lies behind their emigration to Tunisia; it was purely religious, since the Muslim is required to emigrate whenever he feels that his creed is desecrated. This study attempts to exhibit the real reasons behind such emigration by demonstrating the role of the religions factor, and the colonial policy in such decision. Furthermore, the paper presents some other samples of elite emigrants and the challenges they faced there. This Elite comprises: scholars,National armed resistance leaders some Algerian dignitaries